Fire Extinguisher Robot Using Ultrasonic Camera and Wi-Fi Network Controlled with Android Smartphone. (March 2017) - Siregar, B; Purba, H A; Efendi, S; Fahmi, F
Abstract: Fire disasters can occur anytime and result in high losses. It is often that fire fighters cannot access the source of fire due to the damage of building and very high temperature, or even due to the presence of explosive materials. With such constraints and high risk in the handling of the fire, a technological breakthrough that can help fighting the fire is necessary. Our paper proposed the use of robots to extinguish the fire that can be controlled from a specified distance in order to reduce the risk. A fire extinguisher robot was assembled with the intention to extinguish the fire by using a water pump as actuators. The robot movement was controlled using Android smartphones via Wi-fi networks utilizing Wi-fi module contained in the robot. User commands were sent to the microcontroller on the robot and then translated into robotic movement. We used ATMega8 as main microcontroller in the robot. The robot was equipped with cameras and ultrasonic sensors. The camera played role in giving feedback to user and in finding the source of fire. Ultrasonic sensors were used to avoid collisions during movement. Feedback provided by camera on the robot displayed on a screen of smartphone. In lab, testing environment the robot can move following the user command such as turn right, turn left, forward and backward. The ultrasonic sensors worked well that the robot can be stopped at a distance of less than 15 cm. In the fire test, the robot can perform the task properly to extinguish the fire.